Tumor Primary Site and Histology Subtypes Role in Radiotherapeutic Management of Brain Metastases - Khan, Muhammad; Arooj, Sumbal; Li, Rong; Tian, Yunhong; Zhang, Jian; Lin, Jie; Liang, Yingying; Xu, Anan; Zheng, Ronghui; Liu, Mengzhong; Yuan, Yawei (Frontiers in Oncology, 2020)
Randomized controlled trials have failed to report any survival advantage for WBRT combined with SRS in the management of brain metastases, despite the enhanced local and distant control in comparison to each treatment alone. Literature review have revealed important role of primary histology of the tumor when dealing with brain metastases. NSCLC responds better to combined approach even when there was only single brain metastasis present while breast cancer has registered better survival with SRS alone probably due to better response of primary tumor to advancement in surgical and chemotherapeutic agents. Furthermore, mutation status (EGFR/ALK) in lung cancer and receptor status (ER/PR/HER2) in breast cancer also exhibit diversity in their response to radiotherapy. Radioresistant tumors like renal cell carcinoma and melanoma brain metastases have achieved better results when treated with SRS alone. Secondly, single brain metastasis may benefit from local and distant brain control achieved with combined treatment. These diverse outcomes suggest a primary histology-based analysis of the radiotherapy regimens (WBRT, SRS or their combination) would more ideally establish the role of radiotherapy in the management of brain metastases. Molecularly targeted therapeutic and immunotherapeutic agents have revealed synergism with radiation therapy particularly SRS in treating cancer patients with brain metastases. Clinical updates in this regard have also been reviewed.